Preterm birth and maternal psychological health. (November 2015) - Bouras, Georgios; Theofanopoulou, Nikoletta; Mexi-Bourna, Panagioula; Poulios, Antonios; Michopoulos, Ioannis; Tassiopoulou, Ioanna; Daskalaki, Anna; Christodoulou, Christos
Studies have shown that preterm birth significantly influences mothers' psychological health. This study aimed to identify factors associated with preterm birth and assess postnatal depression and anxiety symptoms in mothers of preterm infants ( n = 75) compared to mothers who delivered at term ( n = 125) in a Greek sample. Multiple pregnancies, assisted reproduction technology, caesarean section, non-Greek ethnicity and smoking during pregnancy were associated with preterm delivery. Moreover, preterm infants' mothers had higher depression, state anxiety and trait anxiety scores. These findings suggest that addressing preventable causes of preterm delivery is crucial, while mothers of preterm infants should receive postnatal support.